UPAYA MENINGKATKAN KEPEKAAN SOSIAL MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING PADA PESERTA DIDIK KELAS VII A SMP LABSCHOOL UNESA 3 - Setiawatiningsih, Iyka; Khusumadewi, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The results of observations and interviews with Counselling Guidance teachers obtained more than 50% of Labschool Unesa 3 junior high school students appear to have less respect for the people around them, ignore teacher calls, lack of awareness of the culture of helping, low culture of saying sorry and thank you, and lack of concern for the school environment.  With this condition, it can be concluded that the social sensitivity of students is still low. This research uses a classroom action research method. In this study, data collection methods were used in the form of data from observations of researchers in carrying out actions based on the results of observation sheets in the form of questionnaires and data from direct observations of students. Data analysis techniques in this study used quantitative descriptive data and qualitative descriptive data. Qualitative data analysis was used to obtain a percentage comparison in the first cycle and the second cycle. The results showed that in cycle 1 there were no students who reached classification A, then increased to 42.86% (3 students) in cycle 2. While in classification B, cycle 1 there were 57.14% (4 students), and in cycle 2 there were 42.86% (3 students). In classification C, cycle 1 there were 28.57% (2 learners) and in cycle 2 there were 14.29% (1 learner). In classification D, in cycle 1 there were 14.29% (1 learner) and in cycle 2 there were none. In the E classification in each cycle there is no. Based on the data above, the results of the study have met the success indicators.